Maize management practices and its relationship with nitrogen indexes and yield - Martinez, Dionisio Roberto; Pietrobon, Marianela; Crespo, Cecilia; Stadler, Nicolás; Barbieri, Pablo (Spinger, 2025)
Nitrogen fertilization usually increases maize yields, but its impact varies with water availability and plant density. Nitro¬gen indexes like chlorophyll meter readings may help to predict yield variations. Still, their effect has not been studied under contrasting plant densities, hybrids, and water availability conditions. This study aimed to analyze: (i) maize yield response to nitrogen fertilization across different planting densities and water conditions; (ii) the relationship between nitrogen indexes and yield and its components; and (iii) the effect of hybrids differing in their prolificacy on the relation¬ship between nitrogen indexes and yield. Two experiments (Exp A and Exp B) were conducted using nitrogen fertilization rates and plant densities, Exp A focused on water conditions (irrigation vs. rainfed), while Exp B compared three maize hybrids. The chlorophyll meter readings were determined at different stages. Also, biomass, grain yield, and its compo¬nents were assessed, and their nitrogen nutrition index was determined. Chlorophyll meter readings values were relativ¬ized to compare among the experiments to obtain nitrogen sufficiency index. Increased nitrogen availability consistently increased yield on average by 2599 kg ha− 1 across all plant densities. Changes in density affected nitrogen sufficiency indicators similarly to nitrogen rate variations and water conditions. Higher densities correlated with a 15% lower chloro¬phyll meter readings value. Nitrogen sufficiency index at R4 proved the best predictor of yield variations (R2 = 0.52) and showed a high correlation with nitrogen nutrition index (r = 0.90). Despite hybrids presenting yield differences in optimal densities, responses to nitrogen fertilization both in yield and its components were consistent across hybrids. Plant density induces variations in nitrogen sufficiency index of similar or greater magnitude than nitrogen rates towards. This trend is clearer at the end of the crop cycle that were reflected in similar trends in the nitrogen nutrition index at physiological maturity. Future nitrogen diagnostic methodologies should consider plant density effects on maize response to fertilization